Investigation of healthcare workers attitudes and practices towards the COVID-19 pandemic - Atas, Osman; Yildirim, Tuba Talo; Yildirim, Kadir; Tekin, Samet; Oztekin, Faruk; Gezer, Asime (A. CARBONE Editore, 2020)
Objective: To evaluate the behaviors and attitudes of healthcare workers toward COVID-19. Methods: A total of 280 healthcare workers (172 females and 108 males) answered an online questionnaire about the biosafety procedures for and their attitudes about COVID-19. The average age of participants was 33.57 ± 7.78. The data were analyzed using descriptive statistical methods and the chi-square test. Results: The study sample consisted of 39.5% medical doctors, 32.1% dentists, 14.3% nurses, 4.6% technicians, 2.9% physiotherapists, 3.6% secretaries, and 3.2% auxiliary staff. Of these healthcare workers, 151 (53.9%) had children. A great majority of the participants (91.8%) stated that they were afraid of being infected with the COVID-19 virus. There was no significant difference by gender, but the difference between having a child (95.4%) and not having a child (87.6%) was statistically significant (p=0.042). A little more than half (54.3%) of the participants answered yes to the question of whether they quarantined themselves, and this was found to be significantly higher in those who had children (42.4%) than those who did not (33.3%)(p=0.001). The precautions worn by healthcare workers while working were as follows: masks (89.3%), gloves (80.1%), N95/FFP2 masks (17.4%), face protective shields (39.1%), glasses (28.5%), and bonnets (33.1%). Sources of information for health workers about COVID-19 included the websites or social media accounts of professional organizations such as the Ministry of Health, the Association of Dentists, and the World Health Organization (82.2%); published scientific articles (47.3%); and social media accounts like Instagram and Twitter (48%). Conclusions: While healthcare workers responded well to the standard measures and attitudes they have to protect themselves against COVID-19 contamination, their practice on the extra measures they can take should be improved. In addition to personal protective equipment, efforts should be made to protect the immunity and mental health of healthcare workers. © 2020 A. CARBONE Editore. All rights reserved.
Keywords: Attitudes; COVID-19; Dental education; Dental student